Performance of bottom ash treated peat soil in reducing compressibility - Mohammad Wijdan, Noor Mahadi (2018)
Peat soil is an unsuitable for construction purpose because of its natural properties (high compressibility, low shear strength and high initial water content). This research was done to study the performance of bottom ash treated peat soil in reducing compressibility. The specific amount of OPC (control variable) used as a binders and proportion of bottom ash (manipulate variable) in a series of laboratory test were conducted. This research aims were to determine the relationship between linear shrinkage limit and moisture content of the peat soil before and after stabilization, the relationship between linear shrinkage limit and the fiber content with organic content in peat soil before and after stabilization and to measure the effects of linear shrinkage limit in reducing settlement before and after stabilization. Several test has been done to determine the engineering properties and to obtain the objective of the research such as specific gravity test, pH value test, water content, fiber content, organic content, and linear shrinkage limit. The results proved that Bottom Ash could be used as one of the stabilization agent in reducing the compressibility of the peat soil.